Russian mongolist K. N. Yatskowskaya and the cultural significance of her study of Oirad folk songs - D. Urnokhdelger; Burentsol Burentsol (Nomadic Civilization: Historical Research, 2023)
In this article, the scientist of the Russian Federation K. N. Yatskovskaya’s work on Mongolian studies, including how she recorded and studied Oirad folk songs, was discussed in relation to the characteristics of Oirad Mongolian language and culture. Mongolist K. N. Yatskovskaya in 1988 published a research book called “Mongolian folk songs”. The text consists of two parts: song study and song text. In the research class, folk singers, folk songs, motifs of folk songs, methods of song description, folk poetry and modern poetry were compared. In addition to research, the book is composed of folk song texts, Russian translations of folk songs, folk song chains, a list of the names of singers covered, explanations of words, and bibliography. The book contains 219 Oirad folk songs collected by the author from Khovd and Uvs provinces of Mongolia, and those songs are written in Mongolian Cyrillic letters. Also, 37 songs were selected from these songs and translated into Russian. This book has become a significant and good research, and the 219 folk songs that followed are still very valuable source materials for many scholars of the world who are studying Mongolian folk songs.